2002
DOI: 10.1007/s00330-001-1233-x
|View full text |Cite
|
Sign up to set email alerts
|

Breast MRI for monitoring response of primary breast cancer to neo-adjuvant chemotherapy

Abstract: The objective of the present study was to monitor response to preoperative chemotherapy with breast MRI in patients with large breast cancer. Fifty-eight women in whom core biopsy had confirmed the presence of breast carcinoma underwent breast MRI prior to beginning chemotherapy and before surgical excision. In 24 cases patients underwent one or two additional examinations during chemotherapy to monitor their progress. Breast MRI included both T2-weighted spin-echo sequences and T1-weighted gradient-echo seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
123
0
11

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(136 citation statements)
references
References 22 publications
2
123
0
11
Order By: Relevance
“…This is demonstrated in Table 5a where it is seen that the commonest limitation of the value of CE MRI is to underestimate residual tumour when compared with final pathology. Several authors (Gilles et al, 1994;Drew et al, 2001;Weatherall et al, 2001;Partridge et al, 2002) have found very good prediction of residual tumour by breast MRI, whereas Rieber in two studies had findings similar to ours (Rieber et al, 1997(Rieber et al, , 2002. We wish to seek the explanation for this in greater detail, and will do so by a separate publication studying the dynamic analysis compared with detailed pathology.…”
Section: Discussionmentioning
confidence: 98%
“…This is demonstrated in Table 5a where it is seen that the commonest limitation of the value of CE MRI is to underestimate residual tumour when compared with final pathology. Several authors (Gilles et al, 1994;Drew et al, 2001;Weatherall et al, 2001;Partridge et al, 2002) have found very good prediction of residual tumour by breast MRI, whereas Rieber in two studies had findings similar to ours (Rieber et al, 1997(Rieber et al, , 2002. We wish to seek the explanation for this in greater detail, and will do so by a separate publication studying the dynamic analysis compared with detailed pathology.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have suggested that MRI is a more accurate method of delineating residual tumour following neoadjuvant chemotherapy than clinical, ultrasound or mammographic assessment (Boetes et al, 1995;Abraham et al, 1996;Drew et al, 1999Drew et al, , 2001Fischer et al, 1999;Balu-Maestro et al, 2002;Rieber et al, 2002;Cheung et al, 2003;Rosen et al, 2003;Martincich et al, 2004;Warren et al, 2004). Chemotherapy-induced fibrosis has been shown to impair the evaluation of tumour by conventional radiological methods and physical examination (Cocconi et al, 1984;Segel et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Breast ultrasound, mammography, and clinical examination tend to overestimate the residual tumour volume because of chemotherapy-induced necrosis and fibrosis (Yeh et al, 2005). Magnetic resonance imaging of the breast has been shown to be a sensitive method for visualisation of residual tumour, but the negative predictive value seems to be limited (Abraham et al, 1996;Rieber et al, 2002;Wasser et al, 2003;Denis et al, 2004;Warren et al, 2004;Belli et al, 2006;Segara et al, 2007). There is little information available on the potential role of FDG-PET in the assessment of residual breast cancer following primary chemotherapy.…”
mentioning
confidence: 99%